Modern Imaging Techniques for Early Detection of Retinal Degeneration - Zuhridinovna, Jalalova Dilfuza; Farrukh, Shernazarov (American Journal of Bioscience and Clinical Integrity, 2024)
Obtaining images of the internal anatomical structure of the visual organ is important in ophthalmology, because the diagnosis, treatment and monitoring of patients rely on medical image information. Optical (based on the use of electromagnetic radiation in the optical range) and radiation (using ionizing radiation, magnetic resonance, ultrasound) diagnostic methods are used for visualization in ophthalmology. Technological advances at the end of the 20th century contributed to the emergence of many special diagnostic methods with a very high level of detail of the structures, mainly designed to visualize the posterior segment of the eye. The value of the method of visualization of the anterior segment of the eye * is determined by the main criteria, such as the limits of the field of view, the level of detail of the visual image and the level of reliability of the obtained data. Based on this, when using non-invasive optical methods (biomicroscopy, keratotopography, vitreous endothelium microscopy, corneal confocal microscopy, computer densitometry, gonioscopy, microcycloscopy, microzonuloscopy, retinal peripheral ophthalmoscopy, diaphanoscopy, optical examination of the retina, diaphanoscopy , optical-opticography) anterior segment of the eye), we conditionally distinguish three anatomical zones: well-seen (cornea, conjunctiva, anterior chamber, anterior surface of the iris), partially shown (sclera, anterior chamber angle, lens, central parts of the vitreous) and almost not seen (stroma and iris back surface, objective equator and lens of the ligamentous apparatus, ciliary body, parietal parts of the vitreous body).